2020
DOI: 10.1038/s41598-020-59262-2
|View full text |Cite
|
Sign up to set email alerts
|

The topology and robustness of two Dirac cones in S-graphene: A tight binding approach

Abstract: Present work reports an elegant method to address the emergence of two Dirac cones in a non-hexagonal graphene allotrope S-graphene (SG). We have availed nearest neighbour tight binding (NNTB) model to validate the existence of two Dirac cones reported from density functional theory (DFT) computations. Besides, the real space renormalization group (RSRG) scheme clearly reveals the key reason behind the emergence of two Dirac cones associated with the given topology. Furthermore, the robustness of these Dirac c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Therefore, this insulating phase is distinct from the conventional insulators and we call this phase as topologically non-trivial phase. The systems with Chern numbers ±1 are sometimes referred as Chern insulators [27,34].…”
Section: Topological Phase and Associated Symmetriesmentioning
confidence: 99%
“…Therefore, this insulating phase is distinct from the conventional insulators and we call this phase as topologically non-trivial phase. The systems with Chern numbers ±1 are sometimes referred as Chern insulators [27,34].…”
Section: Topological Phase and Associated Symmetriesmentioning
confidence: 99%
“…In 2012, Wang et al established the stability and electronic characteristics of the armchair and zigzag T-graphene nanoribbons . Besides, extensive research has revealed applications of T-graphene in various intriguing fields, such as in gas sensors, , hydrogen storage, , current rectification devices, and optoelectronic devices. Similar to graphene, the hexagonal forms of Si and Ge are the next two stable candidates from the same group. One of the major advantages of working with silicene and germanene is that considering the spin–orbit coupling effects, the zero-band-gap feature can be avoided. , Recently, the tetragonal counterparts of Si and Ge, i.e., T-Si and T-Ge, have been predicted to be stable on satisfying various stability criteria. Contrary to planar T-graphene, T-Si and T-Ge possess semimetallic band structures with double Dirac cones. , To generate and tune the band gap in these tetragonal systems, several approaches have been taken. , Hence, relative to T-graphene, T-Si and T-Ge are expected to be better candidates for nanodevice applications.…”
Section: Introductionmentioning
confidence: 99%
“…Given these new features of non-Abelian charged degeneracies and multi-gap topological physics, a simple, intuitive, and easily tuneable, but experimentally viable system is of interest. A highlight candidate in this regard are classical spring-mass systems [38][39][40][41][42][43][44][45]. Especially because, if a spring-mass system is constituted in three-dimensional real space, it may exhibit nodal line degeneracies that can have an intricate interplay with non-Abelian charges [22,26].…”
mentioning
confidence: 99%
“…Here, we predict phase transitions of multi-gap nodal lines quantified by Euler class using a class of simple and easily realizable spring-mass systems. The non-Abelian charged nodal lines are realized using phonon waves in a classical spring-mass system [38][39][40][41][42][43][44][45][68][69][70][71][72][73][74]. A unit cell of our system consists of only one mass and several springs, and the system's mechanical behavior is thus described by classical mechanical equations of motion.…”
mentioning
confidence: 99%
See 1 more Smart Citation